2022
DOI: 10.1186/s13287-022-03032-6
|View full text |Cite
|
Sign up to set email alerts
|

Ectoderm-derived frontal bone mesenchymal stem cells promote traumatic brain injury recovery by alleviating neuroinflammation and glutamate excitotoxicity partially via FGF1

Abstract: Background Traumatic brain injury (TBI) leads to cell and tissue impairment, as well as functional deficits. Stem cells promote structural and functional recovery and thus are considered as a promising therapy for various nerve injuries. Here, we aimed to investigate the role of ectoderm-derived frontal bone mesenchymal stem cells (FbMSCs) in promoting cerebral repair and functional recovery in a murine TBI model. Methods A murine TBI model was est… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 71 publications
0
5
0
Order By: Relevance
“…TGFβ1 promotes neurogenesis by promoting quiescent microglia in mouse models of prion disease (Boche et al, 2006;De Lucia et al, 2016). VEGF promotes angiogenesis and tissue repair and decreases inflammatory cytokines in the brain (Xu et al, 2017), and FGF downregulates NF-κB signaling in microglia and decreases astrogliosis in models of traumatic brain injury (Dordoe et al, 2022;Qin et al, 2022). Together, this data suggests that stimulation of AdMSCs with inflammatory cytokines such as TNFα increases their production of protective molecules.…”
Section: Discussionmentioning
confidence: 93%
“…TGFβ1 promotes neurogenesis by promoting quiescent microglia in mouse models of prion disease (Boche et al, 2006;De Lucia et al, 2016). VEGF promotes angiogenesis and tissue repair and decreases inflammatory cytokines in the brain (Xu et al, 2017), and FGF downregulates NF-κB signaling in microglia and decreases astrogliosis in models of traumatic brain injury (Dordoe et al, 2022;Qin et al, 2022). Together, this data suggests that stimulation of AdMSCs with inflammatory cytokines such as TNFα increases their production of protective molecules.…”
Section: Discussionmentioning
confidence: 93%
“…At present, there are no effective therapeutic strategies for severe neurological dysfunction in TBI patients. Numerous works have proven that stem cell therapy and neurogenesis can ameliorate brain injury in experimental models of TBI and other diseases [4 13] . However, the pattern and mechanism of endogenous neuroblasts migration after TBI is still unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Traumatic brain injury (TBI) is a disease with high mortality and morbidity, which leads to severe neurological dysfunction, such as severe motor, neural psychological, and cognitive disabilities [1 4] . Despite extensive researches, there is still no ideal treatment for TBI due to multiple complications during pathogenesis [2 , 4] .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Fibroblast growth factor 1 (FGF1), also known as acid FGF, which is involved in tissue regeneration, trauma repair and metabolism ( Hwang et al, 2022 ; Li et al, 2022 ; Qin et al, 2022 ; Sancar et al, 2022 ). However, in recent years, numerous studies have indicated that FGF1 also appeared to have an effect on the endometrium ( Okumu et al, 2014 ; Kato et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%